Control of the electrophysical characteristics of two-barrier silicon structures with a nanostructured base using gamma radiation - Madatov, R.S.; Abasov, F.P.; Asadov, F.G. (Problems of Atomic Science and Technology, 2023)
During this experimental study, samples of double-barrier structures were irradiated with various doses from a ⁶⁰Co source. The current-voltage characteristics of two-barrier structures from a silicon-based nanostructured base and the change in their spectral photocurrent before and after gamma irradiation were recorded and studied. Experimental results show that voltage values such as open-circuit voltage (Voc) as well as short-circuit current (Isc) and efficiency (η) change with the magnitude of the collection-dissipation voltage.